Human resource management: managing personnel the HRD way - Ghanekar, Anjali (Everest Pub. House, 2011)
Human resource management: managing personnel the HRD way / Ghanekar, Anjali. -- Pune: Everest Pub. House, 2011 658.3 G411e15 15th ed. No. of Copies : 1